Determination of zinc, copper, selenium, and manganese in human milk using acid digestion by ICP-MS and its application in biological trace element monitoring. - Nor Hidayah Mohd Taufek; Awis Sukarni Mohmad Sabere; Ummi Syahidah Mohamad Jamahari; Nur Balkhis Amran; Abdul Rahman Fata Nahas; Joseph Bidai (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: Human milk contains essential trace elements which support healthy development of infants. Previous studies have reported various analytical methods using different instruments to measure trace elements in human milk. This study aimed to determine the trace element concentration in human milk using a validated acid digestion method and its application in biomonitoring. Methods: Human milk samples were collected from three postpartum mothers and prepared using acid digestion method. All samples were analysed using ICP-MS and all validation parameters were measured. Results: Four trace elements which were zinc, copper, manganese and selenium were found to have good linearity (r² > 0.99), limit of detection in µg/L (0.06, 0.0001, 0.005, 0.00003, respectively) and limit of quantification in µg/L (0.18,0.0003, 0.02, 0.0001, respectively). The accuracy (83.4 - 112.7%), inter-day, and intra-day repeatability were within the acceptable limit. The method application on one case study showed the median levels of zinc, copper and selenium in human milk gradually decreased during the early six months, whereas manganese remained stable. Positive significant correlations were observed for most of the elements (r > 0.40, p < 0.001) except for copper-manganese. Conclusion: Acid digestion method is sensitive, accurate and precise to analyse and quantify zinc, copper, manganese and selenium concentrations in human milk simultaneously by ICP-MS. It can be applied in future studies to monitor trace elements concentration in human milk in future studies with larger sample size.